Pengaruh Musim Terhadap Kelimpahan Perifiton Lamun Thallasia hemperichii di Legon Boyo, Karimunjawa - Hendrayana, H; Samudra, Sesilia Rani (Bioma : Berkala Ilmiah Biologi, 2021)
Periphyton abudance is influenced by water dynamics like a currents and waves. The aim of the research was to determaine periphyton abudance on Thallasia hemperichii seagrass in different season waters at Legon Boyo, Karimunjawa. The result show in T. hemperichii were found 9 periphyton classes. The most number is Bacillaryophyceae dominant in every season. Biology index show a value of 0.96-2.6 (low-moderate diversity), uniformity has a value of 0.65-1.48 (medium-high uniformity) and dominance with a value of 0.11-0.23 (low dominance). This shows that the abundance of different periphyton is caused by differences in water dynamics in each season. Â